The Difference in Thyroid Stimulating Hormone Levels between Differentiated Carcinoma and Benign Enlargement - Rianto, Bambang Udji Djoko; Wibowo, Anton Sony; Herdini, Camelia (International Archives of Otorhinolaryngology, 2020)
Introduction Papillary and follicular thyroid carcinoma are common head and neck cancers. This cancer expresses a thyroid stimulating hormone (TSH) receptor that plays a role as a cancer stimulant substance. This hormone has a diagnostic value in the management of thyroid carcinoma.Objective The present study aimed to determine the difference in TSH levels between differentiated thyroid carcinoma and benign thyroid enlargement.Methods The present research design was a case-control study. The subjects were patients with thyroid enlargement who underwent thyroidectomies at the Dr. Sardjito General Hospital, Yogyakarta, Indonesia. Thyroid stimulating hormone levels were measured before the thyroidectomies. The inclusion criteria for the case group were: 1) differentiated thyroid carcinoma, and 2) complete data; while the inclusion criteria for the control group were: 1) benign thyroid enlargement, and 2) complete data. The exclusion criteria for both groups were: 1) patients suffering from thyroid hormone disorders requiring therapy before thyroidectomy surgery, 2) patients receiving thyroid suppression therapy before the thyroidectomy was performed, and 3) patients suffering from severe chronic diseases such as renal insufficiency, and severe liver disease.Results There were 40 post-thyroidectomy case group patients and 40 post-thyroidectomy control group patients. There were statistically significant differences in TSH levels between the groups with differentiated thyroid carcinoma and benign thyroid enlargement (p = 0.001; odds ratio [OR] = 8.42; 95% confidence interval [CI]: 3.19–36.50).Conclusion Based on these results, it can be concluded that there were significant differences in TSH levels between the groups with differentiated thyroid carcinoma and benign thyroid enlargement.
Keywords: thyroid stimulating hormone; thyroid adenoma; thyroid carcinoma; thyrotropin; thyroid neoplasms